2019
DOI: 10.26434/chemrxiv.11400495
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrochemically Triggered Dynamics Within a Hybrid Metal-Organic Electrocatalyst

Abstract: <p> A wide array of systems, ranging from enzymes to synthetic catalysts, exert adaptive motifs to maximize their functionality. In a related manner, select metal-organic frameworks (MOFs) and related systems exhibit structural modulations under stimuli such as the infiltration of guest species. Probing their responsive behavior <i>in-situ</i> is a challenging but important step towards understanding their function and subsequently building from there. In this report, we investigat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In another study, surface enhanced Raman spectroscopy (SERS), as shown in Figure 3D, was utilized in understanding reactivity of Au nanoparticle surfaces toward HMF electrooxidation, yielding DFF as a primary product. 86 Appearance of new spectral bands (338 and 355 cm À1 ) takes place only at potentials >0.8 V (versus Ag/AgCl), within potential range over which surface O x (oxides/hydroxides) form, indicating dependence between HMF oxidation of alcohol moiety and available adsorbed O x * species. These band intensities correspond to alkoxy intermediate, prior to aldehyde formation.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, surface enhanced Raman spectroscopy (SERS), as shown in Figure 3D, was utilized in understanding reactivity of Au nanoparticle surfaces toward HMF electrooxidation, yielding DFF as a primary product. 86 Appearance of new spectral bands (338 and 355 cm À1 ) takes place only at potentials >0.8 V (versus Ag/AgCl), within potential range over which surface O x (oxides/hydroxides) form, indicating dependence between HMF oxidation of alcohol moiety and available adsorbed O x * species. These band intensities correspond to alkoxy intermediate, prior to aldehyde formation.…”
Section: Reviewmentioning
confidence: 99%
“…63,84 (C and D) SFG (C) and SERS (D) spectra respectively, obtained for HMF electrooxidation to study molecular structure and transformations of active species at the electrode/electrolyte interface as influenced by time and potential. 85,86 rise to multiple possible orientations of glycerol adsorption with characteristic spectral fingerprints lying in the region between 1,100 and 1,700 cm À1 , originating from the relevant organic derivatives. 88,89 The diverse spectrum of chemicals of similar molecular structure and functional groups introduces poor discernibility of spectral features and identification of a single corresponding candidate.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation